Analysis of Students’ Quantitative Literacy in Environmental Pollution - Febby Febrianti; Purwati Kuswarini Suprapto; Suharsono Suharsono (Mangifera Edu, 2021)
This study aimed to measure and analyze student quantitative literacy in environmental pollution concept based on six indicators quantitative literacy. This method uses qualitative descriptive. This research was carried out at one of the senior high schools in Tasikmalaya wich is included in one of the schools with cluster one, subject technique was carried out in purposive, whose class has the highest score in biology and mathematics of 30 students. The design used is a case study. This research was done in June 2020. The data collection techniques used to test quantitative literacy refer to the American Colleges and Universities' Association, questionnaire, and interview. Based on data analysis, obtained that of 30 students, two students (6.67%) in the high category, 24 students (80%) in the medium category, and four students (13.33%) in the low category.